2021
DOI: 10.1002/er.6825
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of equivalent circuit model and distribution of relaxation times for fuel cell impedance diagnosis

Abstract: Summary Electrochemical impedance spectroscopy (EIS) is an important diagnostic tool for fuel cells. Accurate extraction of physical parameters from impedance spectra remains a significant challenge for vehicle fuel cells. The reliability analysis results obtained herein revealed that precise identification of middle and low‐frequency impedance by a traditional equivalent circuit model (ECM) was difficult. However, it was determined that the distribution of relaxation times (DRT) could be used to extract three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 40 publications
(53 reference statements)
0
16
0
Order By: Relevance
“…One therefore could expect four corresponding peaks in the DRT spectra. However, in Heinzmann et al (2018), Avioz Cohen et al (2021), and Wang et al (2021), a single oxygen transport peak has been reported. There are two options to explain this result: either some of the oxygen transport peaks overlap with each other (or with the ORR peak) and DRT is not able to separate them, or the codes used were unable to resolve all the transport processes.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…One therefore could expect four corresponding peaks in the DRT spectra. However, in Heinzmann et al (2018), Avioz Cohen et al (2021), and Wang et al (2021), a single oxygen transport peak has been reported. There are two options to explain this result: either some of the oxygen transport peaks overlap with each other (or with the ORR peak) and DRT is not able to separate them, or the codes used were unable to resolve all the transport processes.…”
Section: Introductionmentioning
confidence: 97%
“…Since 2002, a lot of works from the group of Ivers-Tiffée have been devoted to deciphering of solid oxide fuel cell spectra by means of DRT [see a review (Ivers-Tiffee and Weber, 2017)]. Analysis of PEMFC impedance spectra using DRT is a relatively new field (Heinzmann et al, 2018;Avioz Cohen et al, 2021;Reshetenko and Kulikovsky, 2021;Wang et al, 2021). Heinzmann et al (2018) measured impedance spectra of a small (1 cm 2 ) laboratory PEMFC and studied DRT peak behavior depending on cell temperature, relative humidity (RH), oxygen concentration, and current density.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since 2002, a lot of works from the group of Ivers-Tiffée have been devoted to deciphering of solid oxide fuel cell spectra by means of DRT (see a review 6 ). Analysis of PEMFC impedance spectra using DRT is a relatively new field [7][8][9][10] . Heinzmann, Weber and Ivers-Tiffée 7 measured impedance spectra of a small (1 cm 2 ) laboratory PEMFC and studied DRT peaks behavior depending on cell temperature, relative humidity (RH), oxygen concentration and current density.…”
Section: Introductionmentioning
confidence: 99%